2011
DOI: 10.1007/s00464-011-1907-7
|View full text |Cite
|
Sign up to set email alerts
|

A single surgeon’s experience with 54 consecutive cases of multivisceral resection for locally advanced primary colorectal cancer: can the laparoscopic approach be performed safely?

Abstract: No adverse long-term oncologic outcomes of laparoscopic resection were observed in this study. Although inherent limitations exist in this nonrandomized study, laparoscopic multivisceral resection seems to be a feasible and effective treatment option for colorectal cancer for carefully selected patients. Patients with colon cancer should be much more carefully selected for laparoscopic multivisceral resection than patients with rectal cancer because anatomic uncertainty can make oncologic en bloc resection inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
65
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 21 publications
12
65
3
1
Order By: Relevance
“…The authors opined that laparoscopic surgery is feasible with good perioperative outcomes. Kim et al [26] reported their experience in laparoscopic multi visceral resection, including six partial cystectomies, seven seminal vesicle excisions, and three prostatectomies with seminal vesicle resection. Two patients developed urinary fistula following prostatectomy.…”
Section: Extended Resectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors opined that laparoscopic surgery is feasible with good perioperative outcomes. Kim et al [26] reported their experience in laparoscopic multi visceral resection, including six partial cystectomies, seven seminal vesicle excisions, and three prostatectomies with seminal vesicle resection. Two patients developed urinary fistula following prostatectomy.…”
Section: Extended Resectionmentioning
confidence: 99%
“…The indications for MIS have gradually been extended to locally advanced and locally recurrent rectal cancer as a result of technological advances in instrumentation, advances in surgical techniques, increased surgeon experience, and high volume center, which suggested laparoscopic surgery is feasible with good perioperative outcomes [23][24][25] . Kim et al [26] reported that laparoscopic multivisceral resection seems to be a feasible and effective treatment option for colorectal cancer for carefully selected patients without any adverse long-term oncological outcomes. However, safety and feasibility of laparoscopic and robotic surgery in b-TME and e-TME are not well established, and there are very few studies in the world literature.…”
Section: Introductionmentioning
confidence: 99%
“…As Nakafusa et al previously reported that only multivisceral resection was an independent factor for overall postoperative complications (14), extended en bloc multivisceral resection might involve serious complications, leading to an increase in morbidity and mortality. In previous reports, postoperative morbidity and mortality rates after mutivisceral resection tend to be higher ranging from 28.0 to 43.7% (2,8,12,(15)(16)(17) and ≥13% (5,7,12,18), respectively. We observed a postoperative mortality of 4.3% and a morbidity of 39.1% in our study.…”
Section: Discussionmentioning
confidence: 83%
“…All 23 patients received surgery with curative intent. 16 patients received open surgery and seven patients, laparoscopic/robotic surgery. Conversion to open surgery was not required in any of the cases in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Multi‐visceral resection for T4 colorectal cancer has acceptable morbidity and mortality rates and a fair long‐term prognosis 4. Recent reports suggest that minimally invasive techniques for multi‐visceral resection should help achieve adequate short‐term outcomes and improvements in quality of life 5, 6, 7. Here, we describe our experience of complete en bloc resection by anal‐preserving laparoscopic anterior pelvic exenteration in a patient with locally advanced rectosigmoid cancer with direct invasion of the urinary bladder.…”
Section: Introductionmentioning
confidence: 99%